Economic Impact of Allergic Diseases and Asthma-The HEAD Pan-European Registry - Ioana Agache (My University, 2025)
The Health Economics of Allergic Diseases (HEAD) registry is a European-based registry developed by the European Academy of Allergy and Clinical Immunology in collaboration with national allergy societies to facilitate standardised allergic disease management. Using an observational design, this first registry-based study describes care patterns for allergic diseases and their impact on the healthcare system (diagnostic and management costs), society (missed work/school days and disability pension/support) and patients (out-of-pocket costs) in 778 adults and children with allergic rhinitis, asthma, atopic dermatitis and food allergy, from four countries (Belgium, Italy, Romania and Spain). The average total costs per patient and per year were €1329.55 ± 1947.39, with indirect costs of €338.68 ± 1629.61. Direct costs consisted of €82.74 ± 585.90 for hospitalisations, €17.50 ± 125.07 for the emergency department, €172.94 ± 323.17 for specialists, €22.70 ± 132.42 for primary care, €4.85 ± 136.84 for psychologists, €21.24 ± 82.47 for diagnosis and €104.81 ± 469.26 for treatments. Indirect costs were out-of-pocket consultation fees (€16.24 ± 106.40), medications (€161.90 ± 710.58), transportation (€44.15 ± 218.51), private insurance (€16.77 ± 157.91), avoidance (€8.65 ± 92.99) and environmental control (€99.33 ± 955.23). Adults missed 1.02 ± 3.20 workdays, children missed 0.53 ± 2.18 schooldays and burdened their families with 1.38 ± 13.83 lost days. There was a high degree of heterogeneity across countries for management patterns and for costs. The significant burden of allergic diseases calls for immediate action for better management.
Keywords: asthma; allergy; health economic analysis; registry based study